Pertumbuhan Bibit Vanili Akibat Penambahan Zat Pengatur Tumbuh Alami pada Media Tanam yang Diperkaya Bakteri - Kusbianto, Dwi Erwin; Firdaus, Satria Wahyu Ramadhan; Subroto, Gatot; Wulanjari, Distiana; Su’ud, Hasbi Mubarak (Jurnal Agro Industri Perkebunan, 2024)
Propagation of vanilla plants by cutting has been commonly used, but it requires more innovation to overcome the need for many seedlings.  Shortcutting is an alternative solution, but it requires the support of hormones (such as auxin) and adequate planting media. Applying a natural plant growth regulator combined with enriched planting media is expected to increase the growth of shortcutting vanilla seedlings. This research aims to obtain an optimal combination of adding a plant growth regulator and enriched planting media to the growth of shortcutting vanilla seedlings. This study used a factorial Randomized Complete Design (RCD) with three replications. The first factor is the enrichment of planting media consisting of without enrichment (B0), enrichment using Phosphate Solubilizing Bacteria (PSB) (B1), and enrichment using Potassium Solubilizing Bacteria (KSB) (B2). The second factor is without plant growth regulator (J0), using coconut water (J1), and using goat urine (J2). The plant growth was identified for 12 weeks. The data was analyzed using analysis of variance and continued with Duncan’s Multiple Range Test α=5%. The research found interaction in several variables, such as rate of shoot emergence, stem diameter, tendril length, number of foliages, and number of adventitious roots. The combination of PSB and goat urine treatment is the recommended combination because apart from producing interaction with the variables of tendril length, number of foliages, and number of adventitious roots, it is also capable of producing the number, volume, and length of the roots in the soil, also the fresh weight of the plants significantly compared to other treatments. The increase that occurs varies between 20-70%.